APLIKASI INVERS MATRIKS DALAM PEMBENTUKAN PESAN RAHASIA - Syafruddin Side; Syahrana Syahrana (Teknosains, 2015)
One thing that can be improved its implementation inLinear Algebra is Invers Matrix. Two Matrix is invers if two squarematrix have same order, matrix A and B that fulfill the characteristicAB=BA=I, matrix B iscalled multiplication invers from matrix A andit is notated with A-1, just the opposite, matrix A is calledmultiplication invers from B that is notated with B-1. This researchpurpose is to know employing invers matrix in making secret messageby using matrix adjoin to determine invers from a matrix andemploying softwareMicrosoft Visual Basic 6.0 in making message.The steps of employing matrix invers in making secret message are:(1) determining transformation matrix P,(2) secret message is notatedin matrix, (3) multiplying matrix P and Q with the result PQ, (4)matrix is changed into text message with modulus operation (5) toknow sense of the message, the receiver multiplies P-1and matrix PQwith the result the same initial code. When the initial code is same itmeans that the sense of the message is known by the receiver. Theconclusion of the research are; (1) matrix invers by using matrixadjoin is easier than using other method because mathematicsoperation in involving simple operations, in despite of carefulness isneeded. (2) employing invers matrix in making secret message is moreefficient by using softwareMicrosoft Visual Basic 6.0.